Holocene fire-regime changes near the treeline in the Retezat Mts. (Southern Carpathians, Romania). (30th May 2018) - Finsinger, Walter; Fevre, Jordan; Orbán, Ildikó; Pál, Ilona; Vincze, Ildikó; Hubay, Katalin; Birks, Hilary H.; Braun, Mihály; Tóth, Mónika; Magyari, Enikő K.
Abstract: To investigate Holocene vegetation and fire-disturbance histories in the treeline ecotone, macroscopic charcoal, plant-macrofossil, and pollen records from two lacustrine sediment records were used. Lake Lia is on the southern slope and Lake Brazi is on the northern slope of the west-east-oriented Retezat Mountain range in the Romanian Carpathians. The records were used to reconstruct Holocene fire-return intervals (FRIs) and biomass burning changes. Biomass burning was highest at both study sites during the drier and warmer early Holocene, suggesting that climate largely controlled fire occurrence. Fuel load also influenced the fire regime as shown by the rapid biomass-burning changes in relation to timberline shifts. Overall, the number of inferred fire episodes was smaller on the northern than on the southern slope. FRIs were also comparatively longer (1000–4000 years) on the northern slope where Picea abies -dominated woodlands persisted around Lake Brazi throughout the Holocene. On the southern slope, where Pinus mugo was more abundant around Lake Lia, FRIs were significantly shorter (80–1650 years). A period of frequent fire episodes occurred around 1900–1300 cal yr BP on the southern slope, when chironomid-inferred summer temperatures increased and the pollen record documents increased anthropogenic activity near the treeline. However, the forest clearance by burning to increase grazing land was subdued in comparison to other European regions.